An introduction to statistical computing : a simulation-based approach - Voss, Jochen (Chicherter John Wiley, 2014)
"This is a book about exploring random systems using computer simulation and thus, this book combines two different topic areas which have always fascinated me: the mathematical theory of probability and the art of programming computers"--
Includes bibliographical references and index.
Keywords: Mathematical statistics -- Data processing; Statistical computing; MATHEMATICS / Probability & Statistics / General